Reviving rationality saving cost-benefit analysis for the sake of the environment and our health - Livermore, Michael A.; Revesz, Richard L. 1958- (Oxford University Press, 2020)
Reviving rationality: saving cost-benefit analysis for the sake of the environment and our health explains how Donald Trump destabilized the decades-long bipartisan consensus that federal agencies must base their decisions on evidence, expertise, and analysis. Administrative agencies, such as the Securities and Exchange Commission and the Environmental Protection Agency, are charged by law with protecting values like stable financial markets and clean air. Decisions made by these agencies have wide ranging consequences for the well-being of the American public, affecting everything from the safety of workplaces to access to the dream of home ownership. Under the Trump administration, agencies have been hampered in their ability to promote these missions by the conflicting ideological whims of a changing cast political appointees and overwhelming pressure from well-connected interest groups. Inconvenient evidence has been ignored, experts have been side lined, and analysis has been used to obscure facts, rather than inform the public. The results have included haphazard and incoherent policy, social division, defeats in court, a demoralized federal workforce, and a loss of faith in government's ability to respond to the pressing problems facing American society. The hard work of rebuilding a rational regulatory system will fall to future administrations. Norms that the Trump administration has broken should be repaired, and agencies should be set back on the path of reasoned, evidence-based decision making"--